2012
DOI: 10.1159/000339095
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Aspects of Addiction

Abstract: Research has shown that substance use, abuse and addiction are not limited to a specific age group. Problems related to substance addiction are an important cause of morbidity in the population aged 65 years and above, especially the abuse of prescription drugs and legal substances. A lack of evidence-based studies and tailored treatment options for the aging population is evident. Appropriate and effective health care is an important goal to improve the health-related quality of life of elderly people. Resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 43 publications
2
28
0
Order By: Relevance
“…Older adults are particularly prone to opioid toxicity—resulting in complications such as falls and fractures—because of the age-related decline in drug metabolism, their increased exposure to multiple medications, and the high prevalence of multiple co-morbidities. 9-14 Adults ≥ 65 years are the largest consumers of prescription medications, including opioids and other psychoactive drugs. 11-13 …”
Section: Introductionmentioning
confidence: 99%
“…Older adults are particularly prone to opioid toxicity—resulting in complications such as falls and fractures—because of the age-related decline in drug metabolism, their increased exposure to multiple medications, and the high prevalence of multiple co-morbidities. 9-14 Adults ≥ 65 years are the largest consumers of prescription medications, including opioids and other psychoactive drugs. 11-13 …”
Section: Introductionmentioning
confidence: 99%
“…All phenotypes were adjusted for age, gender and the first 10 population principal components to correct for population stratification (Patterson et al, 2006). Age and gender were chosen as covariates in line with the previous literature (Becker and Hu, 2008;Freeman et al, 2017;Grossman et al, 2006;Immonen et al, 2017;Koechl et al, 2012). Age and gender were included as covariates also because they showed an effect on the most part of the investigated phenotypes in our samples (Supplementary Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Comprehensive health care for this group therefore needs to encompass interventions specific to OUD-related issues as well as standard geriatric care. Several authors have suggested the need for specialised training in addiction medicine for geriatricians, and vice versa (Koechl et al, 2012; Rosen et al, 2008). Given our findings, we would add to this a recommendation for access to hepatitis C virus screening, treatment and care.…”
Section: Discussionmentioning
confidence: 99%